Rotation of soybean and Corydalis yanhusuo enhances yield and active compounds of C. yanhusuo via soil nutrient optimisation and rhizosphere microbiome engineering - Liu, Jia; Yuan, Qiang; Zhang, Kejie; Sheng, Xiaoxiao; Zhu, Zixuan; Sui, Ning; Wang, Hui (Frontiers in Plant Science, 2025)
Corydalis yanhusuo W.T. Wang, a herb in the Papaveraceae family used for pain treatment, faces challenges with continuous cropping. Crop rotation with soybean can mitigate soil issues and facilitate the development of subsequent crops. This study evaluated how varying durations of soybean–C. yanhusuo rotation affect yield and active component of C. yanhusuo, soil nutrients, and microbial communities. Rotation with soybean progressively improved yield and active component of C. yanhusuo. Concurrently, soil organic matter, total/hydrolysable nitrogen, and soil enzyme activities improved over time. Microbial OTUs increased in the bulk soil, rhizosphere soil, and roots, along with significant improvements in α-diversity. Over time, the Proteobacteria and pathogenic genera decreased, while Firmicutes and other beneficial genera increased. Network complexity and functions related to nitrate denitrification, cellulolysis, and xylanolysis improved with increased rotation duration. Significant positive correlations were detected between Bacillus, Mortierella, Trichoderma, and yield, medicinal components in C. yanhusuo, and soil nutrients. Structural equation modelling revealed that crop rotation affects C. yanhusuo yield by influencing the microbial community, which in turn alters soil nutrients. The soybean–C. yanhusuo rotation system enhances C. yanhusuo yield and active component content by improving soil nutrients and microbial diversity, providing valuable insights for sustainable medicinal plant cultivation.